Extreme candidates as the beneficent spoiler?: Range effect in the plurality voting system - Wang, Austin Horng-En; Chen, Fang- Yu (Political Research Quarterly)
How does the entrance of radical candidates influence election results? Conventional wisdom suggests that extreme candidates merely split the votes. Based on the range effect theory in cognitive psychology, we hypothesize that the entrance of an extreme candidate reframes the endpoints of the ideological spectrum among available candidates, which makes the moderate one on the same side to be perceived by the voters as even more moderate. Through two survey experiments in the United States and Taiwan, we provide empirical support for range effect in the vote choice in the plurality system. The results imply that a mainstream party can, even without changing its own manifesto, benefit from the entrance of its radical counterpart; it explains why the mainstream party may choose cooperation strategically. Our findings also challenge the assumption in regression models that the perceived ideological positions of candidates are independent of each other. - Reproduced.
Keywords: Voting